Whole body vibration therapy and diabetes type 2: a systematic review and meta-analysis - Fabregat-Fernández, Juan; Rodríguez-Pérez, Vicente; Llamas-Ramos, Rocío; López-Rodríguez, Ana Felicitas; Cortés-Rodríguez, María; Llamas-Ramos, Inés (Frontiers in Endocrinology, 2024)
Background: Vibration platforms have demonstrated systemic effects generated by the use of mechanical vibrations, which are similar to those of any physical activity. The effect that whole body vibration (WBV) generates on the organism could be recommended in Diabetes Mellitus 2 (DM 2) patients.Objective: To systematically review and meta-analyze the available evidence on the effects of WBV on glycemic control in patients with DM 2 Material and Methods: Exhaustive bibliographic searches were carried out until October 2023 in different biomedical portals and databases: Public Medline (PubMed), Scientific Electronic Library Online (SciELO), VHL Regional Portal, Cochrane Central and Latin American and Caribbean Literature in Health Sciences (LILACS). Randomized clinical trials based on the effects of Whole Body Vibration on glycosylated hemoglobin levels, with control group and participants were noninsulin dependent were the inclusion criteria. Two reviewers extracted data independently. A third reviewer was available for discrepancies.Results: Six articles with 223 participants met the criteria and were included in the systematic review; only four of them met the criteria to be part of the meta-analysis. This meta-analysis reveals a positive and significant effect size (μ =0.5731), indicating a substantial difference between the groups studied.Although there is some variability between studies (heterogeneity of 30.05%), the overall direction of the effects is consistent. These findings conclusively suggest the presence of a significant influence of the variable evaluated, underscoring the robustness and consistency of the relationship observed in the literature reviewed.There are no conclusive results due to the lack of data for some variables, which prevents comparison; but WBV may be an effective therapy to improve glycemic control in DM 2 patients.More studies with more patients and longer follow-up are needed.